Let's play games! o jogo como atividade interativa e colaborativa na aprendizagem de inglês por alunos adolescentes de uma escola pública - Araújo, Marco André Franco de (2016)
The main objective of this study is to understand how the use of games can contribute to the learning process in the English language classroom. Three types of games were selected: memory game, board game and describing game and they were performed in a collaborative perspective. The research was conducted in an elementary classroom in a public school in Goiânia in the first and second semesters of 2015 with students who had initial level of knowledge of English as a foreign language. The sociocultural theory was used to support our investigation. From a methodological point of view, we conducted a case study and relied on the qualitative research principles to collect and analyze the data. The results suggest that games contribute to the learning of a foreign language, because, through them, students can co-construct knowledge. We also noted that, through games, students can use strategies that will help them in doing the activities, such as the use of external resources, questions asked to one another and to the teacher, the use of the mother tongue. Games also promote interaction among students, which may make learning more meaningful.